The Cry of the Living Creatures: An Omaha Performance of Blessing - Ridington, Robin (Anthropologica, 2022)
Performance is a powerful language. It speaks through an ordered syntax of studied action. From action it creates "syntaction." This article presents two sets of ethnographic texts that describe a traditional Omaha ceremonial performance. The first is a reconstruction of the 19th-century ceremony inscribing the tattooed Mark of Honour on a young woman whose father is completing initiation into the Night Blessed Society. The second is an epilogue stimulated by critical readings of the first text and based on interviews Jillian Ridington and I conducted in 1985 and 1986 with three elderly Omaha women who bore the Mark of Honour. The information in this study complements material presented in Blessing for a Long Time: The Sacred Pole of the Omaha Tribe (Ridington and Hastings, 1997).